IMPROVING STUDENTS’ ACHIEVEMENT IN WRITING EXPLANATION TEXT THROUGH NUMBERED HEADS TOGETHER (NHT) METHOD - Evin W R Hutasoit; Yunita Agnes Sianipar (Universitas Negeri Medan, 2014)
This study deals with the improvement of the students’ achievement in writing explanation text through Numbered Heads Together (NHT) Method. This study try to find out to what extent using NHT could improve students in writing explanation text. Subject of the study this research, first grade students of SMA NEGERI 1 PEGAGAN HILIR, TIGABARU. There were two kinds of data collected during the study, qualitative and quantitative data. The instrument for collecting the quantitative data was writing test while the qualitative data were diary notes, observation sheet, and questionnaire sheet. The qualitative data showed that the students were interested in the Numbered Heads Together (NHT) Method. Based on the data analysis, the mean of the students score for the first test 52.26, for the second test 69.68, for the third test 79.24 and the last test 82.12. The conclusion is that the Numbered Heads Together (NHT) method can improve the students in writing Explanation text.